Complementary description of the female of Typhlodromus (Anthoseius) xini Wu (Acari: Phytoseiidae) with the first description of its male from Sri Lanka - Ismail Doker, I.; Weliwattage, A.; Jose, A.; Gunasingham, M. (Acarologia, 2024)
Typhlodromus (Anthoseius) xini Wu is reported for the first time in Sri Lanka. Its original description is not very detailed, being based on simple drawings and an absence of diagnostic characters that include chelicera dentition and leg chaetotaxy. Therefore, a complementary description and new illustrations of this species are provided, based on specimens from both sexes collected from Cocos nucifera L. (Arecaceae) infested by spiralling whiteflies in Puttalam District, North Western Province, Sri Lanka. In addition, this is the first discovery and the first description of the unknown male. We also provide a brief comparison between T. (A.) xini and some other species of the subgenus such as T. (A.) diumbokus Schicha & Corpuz-Raros, T. (A.) foraminosus, T. (A.) hartlandrowei Evans, T. (A.) neohartlandrowei Zannou, Moraes & Oliveira, and T. (A.) transvaalensis (Nesbitt). All of these species are similar to each other based on the nature of their dorsal and ventral aspects, chelicera dentition, and spermatheca morphology. Most importantly, ventral seta JV3 is absent in all of these species. In our opinion, it is apparent that all of the aforementioned species share a common ancestor. Therefore, additional molecular analysis, in combination with the use of morphological characters, would help to confirm the taxonomic relationship and evolutionary history of these species. Finally, we also proposed T. (A.) gosabaensis Kar & Karmakar as a new junior synonymy of T. (A.) xini based on the examination of its holotype.
Keywords: Taxonomy; Typhlodromini; Leg chaetotaxy; Synonymy; Indomalayan realm